Kämpfe um Migrationspolitik seit 2015: Zur Transformation des europäischen Migrationsregimes - Kopp, Judith; Graf, Laura; Pichl, Maximilian; Buckel, Sonja; Löw, Neva (transcript, 2021)
»Beyond Summer 15«: European refugee policy, migration regimes and solidarity in civil society in transition.